2018
DOI: 10.1097/ta.0000000000001905
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital low-titer cold-stored whole blood: Philosophy for ubiquitous utilization of O-positive product for emergency use in hemorrhage due to injury

Abstract: The mortality from hemorrhage in trauma patients remains high. Early balanced resuscitation improves survival. These truths, balanced with the availability of local resources and our goals for positive regional impact, were the foundation for the development of our prehospital whole blood initiative-using low-titer cold-stored O RhD-positive whole blood. The main concern with use of RhD-positive blood is the potential development of isoimmunization in RhD-negative patients. We used our retrospective massive tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 10 publications
3
68
0
Order By: Relevance
“…It is interesting that 51% of the centers that use LTOWB would administer RhD‐positive LTOWB to females of childbearing potential whose RhD‐type is either negative or unknown at the time of the transfusion. Perhaps this reflects the adoption of the findings of studies that demonstrated a survival benefit when blood products were administered early in the resuscitation, 6–9 that there are emerging data showing some benefits of transfusing LTOWB, 21–24 and a recognition that hemolytic disease of the fetus and newborn, while still a stressful and emotionally draining diagnosis, is now largely a manageable condition in many parts of the world 25–28 …”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that 51% of the centers that use LTOWB would administer RhD‐positive LTOWB to females of childbearing potential whose RhD‐type is either negative or unknown at the time of the transfusion. Perhaps this reflects the adoption of the findings of studies that demonstrated a survival benefit when blood products were administered early in the resuscitation, 6–9 that there are emerging data showing some benefits of transfusing LTOWB, 21–24 and a recognition that hemolytic disease of the fetus and newborn, while still a stressful and emotionally draining diagnosis, is now largely a manageable condition in many parts of the world 25–28 …”
Section: Discussionmentioning
confidence: 99%
“…LTOWB transfusion is becoming more common, albeit without randomized studies documenting efficacy. 2,16,[24][25][26][27][28][29][30][31][32] However, supply chain issues may complicate timely infectious disease testing. Emergency use of the WBB would not allow for the time (typically requiring 12-24 h after donation) required for complete infectious disease testing.…”
Section: Why Have a Emergency Walking Blood Bank Plan Ready?mentioning
confidence: 99%
“…Our colleagues in San Antonio, Texas, are finalizing their planning; the Royal Caribbean Cruise liners have long utilized such a policy; and the transfusion authorities in Norway have already instituted such a plan and have activated it for several civilian emergencies. 2,4,[24][25][26][27][28][29][30] It is absolutely critical that the use of fresh EUWB described in this plan will be used only for patients with life-threatening bleeding, severe life-threatening anemia, or potentially profound thrombocytopenia. This is defined as a patient who is rapidly and severely bleeding where RBCs, plasma, and platelets are indicated, or anemia so severe as to cause significant signs of cardiovascular stress, or end-organ hypoxemia, and the patient is at risk of imminent death.…”
Section: Introductionmentioning
confidence: 99%
“…The city of San Antonio, Texas, has RhD-positive LTOWB available on many of its emergency medical services' helicopters and ground ambulances. 7,8 Hospitals in other American cities are also implementing LTOWB as their first choice for resuscitating bleeding patients. [9][10][11] One potential logistical concern regarding LTOWB is the quandary of whether to provide RhD-positive or RhD-negative LTOWB to emergency medical services and trauma hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…13 The patient's HLA type might also have a bearing on her RhD-alloimmunization potential. 14 Given that some emergency medical services and hospitals are using RhD-positive LTOWB to treat massively bleeding females of childbearing potential of unknown RhD type, [7][8][9][10][11] the situation will arise whereby mixed-field agglutination will be detected in RhD typing. Mixed-fieldagglutination is a situation whereby some RBCs are F I G U R E 1 Summary of steps to take when a female of childbearing potential of unknown RhD type has been transfused with both RhD positive and RhD negative red blood cells (RBCs)/low titer group O whole blood (LTOWB) before the type and screen sample is drawn.…”
Section: Introductionmentioning
confidence: 99%